PEMILIHAN JENIS KULINER TRADISIONAL SEBAGAI PENDUKUNG PENGEMBANGAN AGROWISATA DI DESA KERTA, KECAMATAN PAYANGAN, KABUPATEN GIANYAR, PROVINSI BALI - Susetia Mahdi, I Made Aries; Satriawan, I Ketut; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret, 2017)
The aim of this research was to determine traditional culinary, the criteria, and the alternative traditional culinary in which could be a priority to support the development of Agrotourism in Kerta Village, Payangan Subdistrict, Gianyar Regency, Province of Bali. This research was conducted from April until July 2016. Using observation and survey method. Traditional culinary in Kerta Village is divided into three types  which are foods, snacks, and beverage. The selection of traditional culinary type uses Analysis Hierarchy Process (AHP). Five experts were chosen to give a score for criteria and culinary alternative. The global priority of food alternative goes to babi guling in the first rank with a score of 0,402 followed by  sate lilit  (score 0.244),  lawar  paku  (score 0.141),  lawar embung  (score 0.102),  sambal matah  (score 0.059), and  nasi sela  with a score of 0.053. The global priority for snacks alternatives in the first rank is rujak with a score of 0,377, followed by  klepon kentang (score 0.157),  klepon  ketela  (score (0.138),  pisang rai  (score 0.123),  ketimus  (score 0.111), and sumping  (score 0.096). The global priority of drink alternatives achieved by  es daluman  as the first priority with a score 0,263, followed  by  kopi luwak  (score 0.196),  es kelapa muda (score 0.180),  loloh kayumanis  (score 0.157),  kopi jahe  (score 0.127) and  loloh tibah  in the last priority with a score of 0.077. Keywords: traditional culinary, agro-tourism, analytical hierarchy process.
Keywords: 133